2018
DOI: 10.1183/13993003.00276-2018
|View full text |Cite
|
Sign up to set email alerts
|

The ROS controversy in hypoxic pulmonary hypertension revisited

Abstract: @ERSpublicationsA study published in the ERJ investigates the role of superoxide in adaptation of the pulmonary vasculature to chronic hypoxia and adaptation of the right ventricle to increased afterload http://ow.ly/Dj9Q30iwO8RCite this article as: Bonnet S, Boucherat O. The ROS controversy in hypoxic pulmonary hypertension revisited. Eur Respir J 2018; 51: 1800276 [https://doi.org/10.1183/13993003.00276-2018.Hypoxic pulmonary vasoconstriction (HPV) is a local and adaptive response to alveolar hypoxia causing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…But the pathogenesis of hypoxic pulmonary hypertension has not been fully understood yet. Overproduction of ROS can result in the progression of pulmonary vascular remodeling [17–19]. H 2 S is an essential small molecule in human physiology.…”
Section: Discussionmentioning
confidence: 99%
“…But the pathogenesis of hypoxic pulmonary hypertension has not been fully understood yet. Overproduction of ROS can result in the progression of pulmonary vascular remodeling [17–19]. H 2 S is an essential small molecule in human physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Although still under debate, CH‐PH has been shown to be associated with a dysregulation of mitochondrial ROS production both in PA and in the heart (Bonnet & Boucherat, 2018; Freund‐Michel et al, 2013, 2014; Pak et al, 2018). In this context, we have evaluated oxidative stress markers in PA and heart from N and CH rats with or without treatment with OP2113 in vivo (Figures 6 and S6).…”
Section: Resultsmentioning
confidence: 99%
“…In the first model, the so-called redox hypothesis, the mitochondrial electron transport chain (ETC) senses hypoxia and decreases ROS production (ROS being produced as an inevitable byproduct of oxidative phosphorylation), causing intracellular calcium influx secondary to redox-sensitive potassium channel inhibition. 113,129 In support of this, Michelakis et al demonstrated that hypoxia and ETC inhibitors suppress the production of activated O 2 species and increase the vasoconstriction of ex vivo pulmonary arteries. 130 The second model is challenged by the ROS hypothesis, which proposes that hypoxia increases mitochondrial ROS generation, mediating elevation of intracellular calcium concentration.…”
Section: Pulmonary Os During Perinatal Hypoxiamentioning
confidence: 89%